Mixed Responses from the International Community to Zimbabwe’s Post 2000 Fast Track Land Reform: Why? (Journal of Governance and Development (JGD), 2019)
Zimbabweâ€™s fast track land reform policy of 2000 brought with it conï¬‚icting responses from the international community. The ï¬rst ten years of independence witnessed the failed willing buyer willing seller model a caveat driven from the Lancaster House Constitution. Britain and USA stopped funding the land reform under the compulsory acquisition era 1991 â€“ 2000. The Lancaster House Constitutional debate failed to address the land issue which remained both an emotional trigger and a national security concern. The revolutionary approach adopted by the ZANU PF Government was induced by the Britishâ€™s creation of the opposition MDC Party. The chaotic nature of the reform attracted backlash from the neoliberals who employed smart power to cripple Zimbabweâ€™s economic sector to rally the population against the ZANU PF-led Government. The generality of Africans identiï¬ed the process in Zimbabwe as critical in redressing the skewed land imbalances engineered by the colonial past. The unresolved road- map to the land redistribution programme, a bilateral issue between Zimbabwe and Britain was internationalised. The competing values in the international communityâ€™s responses to Zimbabweâ€™s fast track land reform policy were kith and kin driven.